2009
DOI: 10.1007/978-3-642-04944-6_1
|View full text |Cite
|
Sign up to set email alerts
|

Scenario Reduction Techniques in Stochastic Programming

Abstract: Abstract. Stochastic programming problems appear as mathematical models for optimization problems under stochastic uncertainty. Most computational approaches for solving such models are based on approximating the underlying probability distribution by a probability measure with finite support. Since the computational complexity for solving stochastic programs gets worse when increasing the number of atoms (or scenarios), it is sometimes necessary to reduce their number. Techniques for scenario reduction often … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 23 publications
0
44
0
Order By: Relevance
“…It is anticipated that implementing formal scenario reduction techniques may become necessary in solving the more challenging multistage problems. 186,[198][199][200][201][202] On a more conceptual level, although the focus of this review is on mathematical programming technique for single-site water network synthesis problems, it can also benefit from concepts in 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 related sub-areas within the domain (and vice-versa). For example, work on hybrid mathematical programming and water pinch analysis techniques 21-22, 24, 69 have shown that the latter (i.e., pinch) can enhance a formulation and reduce model size as well as be exploited in devising solution strategies.…”
mentioning
confidence: 99%
“…It is anticipated that implementing formal scenario reduction techniques may become necessary in solving the more challenging multistage problems. 186,[198][199][200][201][202] On a more conceptual level, although the focus of this review is on mathematical programming technique for single-site water network synthesis problems, it can also benefit from concepts in 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 related sub-areas within the domain (and vice-versa). For example, work on hybrid mathematical programming and water pinch analysis techniques 21-22, 24, 69 have shown that the latter (i.e., pinch) can enhance a formulation and reduce model size as well as be exploited in devising solution strategies.…”
mentioning
confidence: 99%
“…Since for low values of , D attains a large value, in order to handle the emerging computational complexity issues, we have performed scenario reduction. Our scenario reduction method is based on the concept of probability distance and follows the lines of the methodology in [33], using the Chebyshev distance to determine the similarity of two scenarios. According to this methodology, the reduced set of scenarios lies close in probability distance to the initial set including all scenarios.…”
Section: H Determination Of the Number Of Scenariosmentioning
confidence: 99%
“…To overcome this problem, many well-known scenario reduction methods have been put forward [36][37][38][39][40]. Römisch, et al [37] reviewed available scenario reduction techniques and discussed the related open problems.…”
Section: Wind Power Scenario Reduction Strategymentioning
confidence: 99%
“…Römisch, et al [37] reviewed available scenario reduction techniques and discussed the related open problems. This paper chooses the Kantorovich distance method [27,39], and sets to minimize the Kantorovich distance between the initial scenario and the removed scenario as the reduction objective.…”
Section: Wind Power Scenario Reduction Strategymentioning
confidence: 99%